2020
DOI: 10.15366/archaeofauna2020.29.005
|View full text |Cite
|
Sign up to set email alerts
|

Continuities and changes of animal exploitation across the Bronze Age – Iron Age boundary at mining sites in the Eastern Alps

Abstract: Since the 1990s, the Schwaz-Brixlegg mining district in the Lower Inn Valley, North Tyrol, Austria, features excavations on mostly Late Bronze (LBA) to Early Iron (EIA) Age sites, focusing on the reconstruction of metallurgic activities and of all aspects related to it. This paper reviews the Schwaz-Brixlegg archaeozoological materials and compares them with those from contemporaneous mining (copper and salt) sites on the Eastern Alps, to assess diet and subsistence strategies of the early alpine, geo-resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results from Prigglitz fit into this general Bronze Age pattern [ 6 , 10 , 19 ] concerning the miners’ obvious preference for pork for meat consumption. Recent studies have revealed a change in dominant meat categories at the beginning of the Early Iron Age [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results from Prigglitz fit into this general Bronze Age pattern [ 6 , 10 , 19 ] concerning the miners’ obvious preference for pork for meat consumption. Recent studies have revealed a change in dominant meat categories at the beginning of the Early Iron Age [ 20 ].…”
Section: Introductionmentioning
confidence: 99%